Context-Based Leisure Travel Facilitation among People with Mobility Challenges: A Self-Determination Theory Approach. (January 2019) - Zhang, Ye; Cole, Shu; Ricci, Peter; Gao, Jie
In response to the pressing need to psychologically empower people with mobility challenges (PwMC) to travel, this study proposes the facilitation of self-determined travel motivations as a promising approach. The variation of self-determined travel facilitation across different challenge levels is examined through a quasi-experimental design and analyzed with a new test of moderated mediation based on Hayes' (2015a) model. The results indicate that for PwMC with significant travel challenge levels, the tourism industry should prioritize the cultivation of intrinsic travel motivations and perceived travel competence satisfaction over less-autonomous motivation dimensions and satisfaction of alternative psychological needs. Such cross-context exploration extends self-determination theory with a new moderator of challenge levels. The adopted new analysis of moderated mediations is competitive regarding accuracy, efficiency, and robustness for less-controlled, real-world tourism experiments. Results can also guide the customization of motivational programs for different PwMC to maximize the effectiveness of psychological empowerment for travel.